It is time to test low level laser therapy in Great Britain. Issue 957 (5th July 2005) - Moshkovska, T; Mayberry, J
Abstract : Low level laser therapy (LLLT) has been used in Eastern Europe and Asia for the treatment of a wide range of conditions for many years. Its continued acceptance in these populations reflects the efficacy with which it is regarded both by clinicians and their patients. Although there have been a substantial number of reports on its clinical benefit and some practitioners have used the technique in North America and Australasia it has yet to be subjected to detailed assessment through randomised clinical trials. The purpose of this review is to stimulate interest in the technique and to encourage rigorous research into its potential value.